Structural diversities and magnetic properties of a series of Fe(II) coordination polymers based on bis(triazole) ligands. (18th April 2015) - Qi, Jing; Tong, Yu-Zhang; Tang, Guo-Tao; Wang, Qing-Lun; Li, Li-Cun; Ma, Yue; Yang, Guang-Ming; Liao, Dai-Zheng
Graphical abstract: Five bis(triazole)-Fe(II) coordination polymers have been synthesized and structural characterized. As increasing the length of the ligands, the corresponding Fe(II) coordination polymers transit from 1D to 2D structure. The iron(II) ions all remain in the high spin state down to 2 K and the experimental data were fitted by using the single ion approximation for Fe(II) ion with zero-field splitting of ground-state quintet. Abstract: A series of bis(triazole)-Fe(II) coordination polymers, [Fe(NCS)2 (btm)2 ]·H2 O n (1 ), [Fe(bte)2 (NCS)2 ][Fe(bte)(H2 O)2 (NCS)2 ] n (2 ), [Fe(NCS)2 (btp)2 ] n (3 ), [Fe(NCS)2 (btb)2 ] a [Fe(NCS)2 (btb)2 ] b n (4 ) and [Fe(NCS)2 (bth)2 ] n (5 ) (btm = bis-(1, 2, 4-triazol-1-yl)methane, bte = 1, 2-bis-(1, 2, 4-triazol-1-yl)ethane, btp = 1, 3-bis-(1, 2, 4-triazol-1-yl)propane, btb = 1, 4-bis(1, 2, 4-triazol-1-yl)butane, bth = 1, 6-bis(1, 2, 4-triazol-1-yl)hexane), have been synthesized and structural characterized by X-ray single-crystal diffraction. Compounds1 –3 are 1D chains, complex4 is a mixture of 2D networks and 1D chains, while complex5 has 2-fold interpenetrated frameworks of [Fe(NCS)2 (bth)2 ] n 2D planes. The iron(II) ions in complexes1 –5 all remain in the high spin state down to 2 K and the experimental data were fitted by using the single ion approximation for Fe(II) ion with zero-field splitting of ground-state quintet.